2021
DOI: 10.1186/s12885-021-09083-x
|View full text |Cite
|
Sign up to set email alerts
|

ESR1 PvuII polymorphism: from risk factor to prognostic and predictive factor of the success of primary systemic therapy in advanced breast cancer

Abstract: Background The ESR1 gene encodes Estrogen Receptor alpha (ERα), which plays a role in the tumourigenesis of breast cancer. A single nucleotide polymorphism (SNP) in intron 1 of this gene called ESR1 PvuII (rs2234693) has been reported to increase the risk of breast cancer. This study aimed to investigate the ESR1 PvuII polymorphism as a prognostic and predictive factor guiding the choice of therapy for advanced breast cancer. Methods This retrospec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 28 publications
0
4
0
Order By: Relevance
“…Several studies have shown that CXCL11, CXCL13, and CXCL14 biomarkers are closely related to chemotherapeutic resistance in BC (29)(30)(31)(32)(33). ESR1 encodes estrogen receptor α (ERα) and plays an important role in the tumorigenesis of BC (34). The vast majority of BCs are ER positive and endocrine sensitive but not sensitive to chemotherapy (35,36).…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have shown that CXCL11, CXCL13, and CXCL14 biomarkers are closely related to chemotherapeutic resistance in BC (29)(30)(31)(32)(33). ESR1 encodes estrogen receptor α (ERα) and plays an important role in the tumorigenesis of BC (34). The vast majority of BCs are ER positive and endocrine sensitive but not sensitive to chemotherapy (35,36).…”
Section: Discussionmentioning
confidence: 99%
“…Our study revealed that breast patients who carried AhR (GG), Xbal (AA), and PvuII (TT) genotypes had a better prognosis, this agreed with findings of previous studies. 4,11,16 In conclusion, the polymorphic variation of positive genotypes of PvuII, XbaI, and AhR polymorphisms is highly associated with better prognosis in breast cancer patients. Negative genotypes of PvuII, XbaI, and AhR polymorphisms are strong and significantly prevalent in poor-prognostic breast cancer patients…”
Section: Discussionmentioning
confidence: 85%
“…Genetic variation T/C of the PvuII polymorphism of the ESR1 gene may be a risk factor for hepatocellular carcinoma, gallbladder cancer [46], breast cancer [10,47], and endometrial cancer [48]. Genotypes T/C and C/C for the PvuII polymorphism of the ESR1 gene give a poor prognosis in advanced breast cancer, but they can be considered a good predictor of the therapeutic effect of hormone therapy [49,50]. The PvuII polymorphism of the ESR1 gene can change susceptibility to endometrial cancer [51].…”
Section: Discussionmentioning
confidence: 99%